Application of Vertical Electrical Sounding (VES) Resistivity Method to determine a well recommendation point at deep-groundwater exploitation - Taufiq Taufiq; Maharani Maharani; H D Mega (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
The demand of fresh water to develop of life community is very important, where almost all construction activities is required a water such as irrigating rice fields, building infrastructure, and to daily consumption. To obtain a good quality of groundwater, several parameter must be specified such as the depth of groundwater, thickness of the source, and resistivity value of rock. In this case, we try to applied Vertical Electrical Sounding (VES) resistivity method with Schlumberger configuration on one of Pamsimas Project to answer that parameter. VES Resistivity method is one of the active methods in geophysical study based on electrical properties of the subsurface rock by injecting electric current (I) into the earth and record the potential difference (?V) produced to the surface. From the results of current and potential difference measurements for each electrode spacing (AB/2) different then be lowered resistivity variations in the value of each layer below the measuring point (sounding points). After the acquisition on 3 points at Pandansari Village (PS-01, PS-02, PS-03), we get the result on PS-01, the water layer is indicated on the depth 60-80 meters with resistivity values equal than 36.7-50 ?m. On PS-02, the water layer is indicated on the depth 50-100 meters with resistivity values equal than 18.7-40 ?m. On PS-03, the water layer is indicated on the depth 30-60 meters with resistivity values equal than 52.8-70 ?m. Afterthat, we run 2D-pseudosection to know the distribution of groundwater layer in subsurface and get the thickness of groundwater is 20-50 meter with depth 40-80 meter. Based on this result, the PS-01 is the best point to make a well-exploitation on South Pandansari Pamsimas Project.